De lo duradero a lo perecedero, I: Las improntas textiles en la cerámica de Esmeraldas, Ecuador - Guinea Bueno, Mercedes (Revista Española de Antropología Americana, 2003)
The textile impressions in some of the ceramic objects recovered by the «Proyecto Esmeraldas», contribute us valuable information on the prehispanic textile techniques in the north coast of the Ecuador, and offer hypothesis on the existence in the zone of different specialists: ceramists in the Formative period and weavers in the Regional Development period.
Keywords: Textile impressions; Northern Andes; Prehispanic; Ecuador